2005
DOI: 10.1515/bc.2005.115
|View full text |Cite
|
Sign up to set email alerts
|

Unusual reactions involved in anaerobic metabolism of phenolic compounds

Abstract: Aerobic bacteria use molecular oxygen as a common co-substrate for key enzymes of aromatic metabolism. In contrast, in anaerobes all oxygen-dependent reactions are replaced by a set of alternative enzymatic processes. The anaerobic degradation of phenol to a non-aromatic product involves enzymatic processes that are uniquely found in the aromatic metabolism of anaerobic bacteria: (i) ATP-dependent phenol carboxylation to 4-hydroxybenzoate via a phenylphosphate intermediate (biological Kolbe-Schmitt carboxylati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
35
0
6

Year Published

2007
2007
2017
2017

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 48 publications
(42 citation statements)
references
References 49 publications
(65 reference statements)
0
35
0
6
Order By: Relevance
“…In these experiments, nitrate was used as the electron acceptor for two reasons. In a previous study, it was shown that (i) oxidation of resorcinol and HHQ was dependent on electron acceptors with a positive redox potential such as K 3 Fe(CN) 6 and nitrate (32) and (ii) nitrate was the only electron acceptor that did not react chemically with HHQ (32). Nitrate was used in excess to provide an electron acceptor for the first two reactions, namely, resorcinol hydroxylation and HHQ dehydrogenation, and to provide an electron acceptor for potential oxidations involved in the further degradation of HBQ.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…In these experiments, nitrate was used as the electron acceptor for two reasons. In a previous study, it was shown that (i) oxidation of resorcinol and HHQ was dependent on electron acceptors with a positive redox potential such as K 3 Fe(CN) 6 and nitrate (32) and (ii) nitrate was the only electron acceptor that did not react chemically with HHQ (32). Nitrate was used in excess to provide an electron acceptor for the first two reactions, namely, resorcinol hydroxylation and HHQ dehydrogenation, and to provide an electron acceptor for potential oxidations involved in the further degradation of HBQ.…”
Section: Resultsmentioning
confidence: 99%
“…Resorcinol hydroxylase and hydroxyhydroquinone dehydrogenase enzyme activities were measured at 30°C under anoxic conditions as previously described (32), except that potassium phosphate buffer (50 mM, pH 7.0) was used as the buffer in all of the assays. A standard reaction mixture used to assay resorcinol hydroxylase contained 0.2 to 0.3 mg of protein, 1 mM K 3 Fe(CN) 6 , and 1 mM resorcinol. A standard reaction mixture used to assay hydroxyhydroquinone dehydrogenase contained 0.2 to 0.3 mg of protein, 1 mM NaNO 3 , and 1 mM resorcinol.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…In this strain, phenol is initially converted to phenylphosphate by phenylphosphate synthase (Pps) with concomitant hydrolysis of ATP (5,16,28) (Fig. 1A).…”
mentioning
confidence: 99%